Determining the loading on the body of a covered wagon modernized for container transportation - Panchenko, Sergii; Lovska, Alyona; Muradian, Arsen; Pelypenko, Yevhen; Romakh, Valentyna (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the process of loading the body of a covered hopper railroad car, modernized for container transportation. The task addressed is to improve the efficiency of container transportation by rail. To this end, it is proposed to use covered wagons taking into account the modernization of their structure. The modernization involves dismantling the roof and placing fitting stops on the floor for fastening containers. The study was conducted using a universal covered wagon, model 11-217, as an example. The strength of the covered wagon body was calculated when it is subjected to vertical loads from containers, as well as the simultaneous action of vertical and longitudinal loads. It was established that when the body of the covered wagon is subjected to vertical loads, the maximum stresses in its structure are 8.3% lower than the permissible ones. When vertical and longitudinal loads are simultaneously applied, the maximum stresses in the body are 4% lower than the permissible ones. The calculation results prove that the strength of the covered wagon body, taking into account the proposed modernization, is maintained. A feature of the proposed modernization is the fact that, if necessary, the design of the covered wagon body can be returned to its original state. The scope of practical application of the results is railroad transport. A condition for using the findings is the symmetrical placement of the fitting stops relative to the transverse axis of the covered wagon body, which is due to the need to ensure uniform loading of both car bogies. This study will contribute to increasing the efficiency of container transportation by rail and container transportation in general